Literatur Review: Analisis Profil Miskonsepsi Pada Peserta Didik SMA Pada Materi Fisika Listrik Dinamis - Irman Muliadi; Neli Yuliani (Indonesian, 2025)
Physics is a branch of science developed through experiments and theoretical explanations to describe natural phenomena. In high school physics education, one of the critical topics is dynamic electricity due to its relevance to everyday life. However, misconceptions among students regarding fundamental concepts of dynamic electricity pose significant challenges. This study aims to identify and analyze the profiles of students' misconceptions in dynamic electricity and propose teaching strategies to address them. The research employs a systematic literature review method by analyzing 355 articles from various relevant national journals. The findings reveal several major misconceptions, such as misunderstandings of Ohm's law, current and voltage in series-parallel circuits, and the use of electrical measuring instruments. The primary causes of these misconceptions are a lack of fundamental understanding, limited practical experience, and less effective teaching approaches. This study concludes that preventing and addressing misconceptions requires a more interactive teaching approach, experiment-based learning, and the use of digital simulations. Teachers are encouraged to utilize these research findings to improve teaching quality and minimize misconceptions in the future. This article also provides insights into the relationship between teaching methods and the curriculum used, making it a valuable reference for developing more effective physics education strategie.